THE EFFECTIVENESS OF PRECONDITIONING AND POSTCONDITIONING WITH ADENOSINE IN PREVENTION OF REPERFUSION DAMAGE IN PATIENTS WITH ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - N. T. Vatutin; A. N. Shevelok; V. S. Kolesnikov (Архивъ внутренней медицины)
The study aimed to evaluate the effectiveness of pharmacological preconditioning and postconditioning with sublingual adenosine in prevention of reperfusion damage in patients with ST-segment elevation myocardial infarction.Material and methods. In prospective trial 166 patients with STEMI were randomized to sublingual adenosine prior and after  percutaneous coronary intervention (n=82) or standard therapy  (n=84). Reperfusion arrhythmia, blood level of troponin T and effectiveness of reperfusion was assessed.Results. According to PCI results angiographic success was achieved in 88.1% patients of adenosine group and 92.7% patients of  standard therapy group (p > 0.05). The reperfusion arrhythmias rate was significantly low in adenosine group (78%) compared to control  (92.9%, p = 0.013). The use of adenosine was associated with  25.4% risk reduction in life-threatening reperfusion arrhythmias  (p<0.01). During 24 h after PCI troponin T level decreased in both  groups more significantly in adenosine (p < 0.05). The use of  adenosine was associated with 8.3% risk reduction in myocardial  reperfusion damage (p < 0.05).Conclusions. The pharmacological preconditioning and  postconditioning with sublingual adenosine in the perioperative  period of PCI in patients with STEMI is usefull to prevent myocardial reperfusion damage but does not affect the efficiency of reperfusion.